Interictal Spikes and Epileptogenesis - Staley, Kevin J (Blackwell Science Inc, 2006)
Interictal spikes are widely accepted diagnostically as a sign of epilepsy, but reasons for the presence of interictal activity in the epileptic brain are unknown. Interictal spikes are easily generated in normal brain by pharmacologically reducing inhibition, and experimental studies of acquired epilepsy indicate that spikes precede seizures. These data lead to the hypothesis that interictal spikes are correlated with epilepsy because they play a fundamental role in epileptogenesis following brain injury. Spikes may guide sprouting axons back to their network of origin, increase and sustain the strength of the synapses formed by sprouted axons, and alter the balance of ion channels in the epileptic focus, such that seizures become possible. This hypothesis has implications that are testable: altering spiking or the calcium signals generated by spikes should alter epileptogenesis and spikes should precede seizures in brain-injured human patients.